Reirradiation in progressive high-grade gliomas: outcome, role of concurrent chemotherapy, prognostic factors and validation of a new prognostic score with an independent patient cohort - Scholtyssek, Felix; Zwiener, Isabella; Schlamann, Annika; Seidel, Clemens; Meixensberger, Jürgen; Bauer, Manfred; Hoffmann, Karl-Titus; Combs, Stephanie; von Bueren, André O.; Kortmann, Rolf-Dieter; Müller, Klaus (Radiation oncology, 2013)
First, to evaluate outcome, the benefit of concurrent chemotherapy and prognostic factors in a cohort of sixty-four high-grade glioma patients who underwent a second course of radiation therapy at progression. Second, to validate a new prognostic score for overall survival after reirradiation of progressive gliomas with an independent patient cohort.
Gesehen am 15.07.2021